Glucocorticoid use during cardiopulmonary resuscitation may be beneficial for cardiac arrest. (1st November 2016) - Tsai, Min-Shan; Chuang, Po-Ya; Yu, Ping-Hsun; Huang, Chien-Hua; Tang, Chao-Hsiun; Chang, Wei-Tien; Chen, Wen-Jone
Abstract: Background: Various studies have indicated that glucocorticoid supplementation during cardiopulmonary resuscitation (CPR), in conjunction with vasopressors, may improve outcomes in instances of cardiac arrest. However, further population-based analysis is warranted with respect to resuscitative and long-term survival benefits conferred by administering glucocorticoids in this setting. Methods: A total of 145, 644 adult patients who experienced non-traumatic, cardiac arrest occurred at emergency room during years 2004–2011 were selected for study from the Taiwan National Health Insurance Research database. These patients were grouped as steroid and non-steroid recipients during CPR, and group members were matched in terms of patient characteristics, including presenting complaint, prior steroid use, resuscitative drugs and shocks delivered, treatment setting (medical center or not), socioeconomic status, and year that cardiac arrest occurred, through propensity scoring. Logistic regression analysis was performed to determine the impact of steroid usage on survival to admission, survival to discharge, and 1-year survival. Results: Compared with matched non-steroid group members (n = 8628), patients given steroid (n = 2876) displayed significantly higher rates of survival to admission (38.32% vs 18.67%; adjusted OR = 2.97, 95% CI 2.69–3.29; p  < 0.0001), survival to discharge (14.50% vs 5.61%; adjusted OR = 1.71, 95% CI 1.42–2.05; p  < 0.0001), and 1-year overall survival (10.81% vs 4.74%; adjusted OR = 1.48, 95% CI 1.22–1.79; p  < 0.0001). Steroid use proved more beneficial in patients with COPD or asthma and in the absence of shockable rhythm during CPR. Conclusion: Glucocorticoid use during CPR is associated with improved survival-to-admission, survival-to-discharge, and 1-year survival rates.